APHORISMS AS A CULTURAL ESSENCE OF THE LANGUAGE - Ashurova Feruza Lutpullaevna (Western European Studies, 2024)
This article examines the linguocultural features of aphorisms. Aphorisms are the cultural essence of language, generalized and developed by the sages, the richest spiritual soil of man, capable of inspiring, admonishing, enlightening, which is the spiritual enrichment of people. Aphorisms include inspiring aphorisms, philosophical aphorisms, literary aphorisms, etc. Aphorisms can be used for a variety of purposes, not only to study linguocultural elements or study their content, but also as a capacious expression in persuasive discourse with many pragmatic purposes
Keywords: aphorisms; linguoculturology; saying; pragmatics